2021
DOI: 10.1186/s13059-021-02266-6
|View full text |Cite|
|
Sign up to set email alerts
|

CRISPRi enables isoform-specific loss-of-function screens and identification of gastric cancer-specific isoform dependencies

Abstract: Introduction Genes contain multiple promoters that can drive the expression of various transcript isoforms. Although transcript isoforms from the same gene could have diverse and non-overlapping functions, current loss-of-function methodologies are not able to differentiate between isoform-specific phenotypes. Results Here, we show that CRISPR interference (CRISPRi) can be adopted for targeting specific promoters within a gene, enabling isoform-spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 46 publications
0
16
0
Order By: Relevance
“…2I). We have previously reported that bidirectional promoters can result in off-target effects in CRISPRi screens (Davies et al, 2021;Rosenbluh et al, 2017), and in some cases we found inconsistencies that are likely due to off-target effects. For example, ATXN7 scored as a strong tumorsuppressor gene using CRISPRko in both 2D and 3D assays but did not score with CRISPRi (Supplementary Fig.…”
Section: Bc Associated Risk Genes That Upon Suppression or Overexpression Induce Cell Proliferation Phenotype In 2d And 3d Culturesmentioning
confidence: 62%
See 2 more Smart Citations
“…2I). We have previously reported that bidirectional promoters can result in off-target effects in CRISPRi screens (Davies et al, 2021;Rosenbluh et al, 2017), and in some cases we found inconsistencies that are likely due to off-target effects. For example, ATXN7 scored as a strong tumorsuppressor gene using CRISPRko in both 2D and 3D assays but did not score with CRISPRi (Supplementary Fig.…”
Section: Bc Associated Risk Genes That Upon Suppression or Overexpression Induce Cell Proliferation Phenotype In 2d And 3d Culturesmentioning
confidence: 62%
“…High-throughput sequencing library was generated using one-step PCR to amplify the integrated sequence within the construct and the addition of a barcode as previously described (Davies et al, 2021;Rosenbluh et al, 2016;Rosenbluh et al, 2017). PCR products were then purified using AMPure beads and samples sequenced using HiSeq (Illumina).…”
Section: Library Preparation Sequencing and Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…For each gene we chose top scoring 5 sgRNAs (based on CRISPick scores). Libraries were prepared as previously described 22,23,67 . Briefly, oligonucleotide pools (CustomArray) contained the sgRNA sequence appended to BsmBI cutting sites and overhang sequences for PCR amplification.…”
Section: Discussionmentioning
confidence: 99%
“…4A). The inconsistencies detected are likely due to CRISPRi bidirectional promoter off-target effects 22,23 . For example, ATXN7 scored as a strong tumor-suppressor using CRISPRko in 2D and 3D assays but did not score with CRISPRi (Extended Data Fig.…”
Section: Bc Risk Genes That Induce a Proliferation Phenotype In 2d And 3d Culturesmentioning
confidence: 99%